Lunch hour - Mortimer, John Clifford 1923-2009; Field, Shirley Anne 1936-2023; Stephens, Robert 1931-1995 (BFI, 2011)
"Shirley Anne Field gives an unforgetable, fiery performance as a young designer on the brink of an affair with a married male executive (Robert Stephens) at the company where she works. With a tightly focused plot telling the story of an illicit lunch-hour rendezvous in 'real time', Lunch Hour is presented here in a stunning new High Definition transfer, and is accompanied by three of James Hill's delightful, award-winning colour shorts."
Verlagsnummer BFIB1042
Original: UK 1962
Bildformat 1.66:1
Special features: Presented both in High Definition and Standard Definition ; Skyhook (James Hill, 1958, 17 min): the adventure of oil exploration, deep in the tropics of Papua New Guinea ; Giuseppina (James Hill, 1959, 32 min): Oscar-winning short in which a young girl observes the array of quirky characters who pass her father's rural petrol station ; The Home-Made Car (James Hill, 1963, 28 min): a man restores his dilapidated Bullnose Morris, under the watchful eye of a curious young neighbour ; Booklet with essays by Sue Harper and James Piers Taylor
Keywords: Film; DVD-Video; Blu-Ray-Disc